Powered Toothbrushes: An Opportunity for Biofilm and Gingival Inflammation Control - Cassiano Kuchenbecker Rösing; Eduardo Garduño; Sandra Kalil Bussadori; Agustín Zerón; Paulo Vinícius Soares; Marc Saadia; Cristina Cunha Villar (International Journal of Dentistry)
The present review aimed at a broad investigation on the potential of powered as compared to manual toothbrushes in different aspects of clinical dentistry. Studies evaluating plaque and gingival inflammatory parameters were included, as well as those that investigated adverse effects. Emphasis was given separately to adults, youngsters, special-needs patients, and those under fixed orthodontic therapy. In general, comparisons favored powered toothbrushes. In summary, approximately 68% of the included studies, in terms of plaque/gingival inflammation in adults, presented better results for powered toothbrushes. In children and special-needs populations, approximately 40% of the included studies favored powered toothbrushes for plaque/gingival inflammation, and none favored manual ones. In orthodontic individuals, 50% of the studies also demonstrated a better effect of powered toothbrushes on plaque and gingival inflammation. All included studies that assessed adverse events did not demonstrate a difference in these effects when comparing manual vs. powered toothbrushes. It is concluded that the use of powered toothbrushes is an opportunity to enhance patterns of plaque control and associated gingival inflammation.